Proof-of-concept for Site-specific Delivery of Mesalamine Nanoparticles for Effective Therapy in Colitis - Sreeharsha, Nagaraja; Narayan, Rashmi; Vijaya, Joshi; Nair, Anroop (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: Mesalamine loaded polymeric nanoparticles were prepared using three different polymers namely, Eudragit RS100, PLGA (50:50), or Eudragit RLPO, with an aim of targeted delivery to the inflamed colon. Materials and Methods: Nanoparticles were prepared by modified emulsification solvent evaporation and characterized for various physicochemical characteristics viz., size, size distribution, mesalamine entrapment, and in-vitro release. Results: Amongst the various formulations prepared, formulation F5 mesalamine nanoparticles made with Eudragit RS100 showed drug entrapment of 72.09% with comparative discrete nearing spherical particle size of 200 nm. In-vivo targeting potential of nanoparticles to the inflamed tissue was evaluated in acetic acid-induced colitis rat model and efficacy was compared with pristine mesalamine powder. Biochemical estimations were carried in colonic tissue homogenate to check the oxidative damage. The myeloperoxidase activity and lipid peroxides were significantly decreased and glutathione content increased after the oral administration of mesalamine nanoparticles compared to pure drug mesalamine. Conclusion: This delivery system enabled the drug to accumulate in the inflamed tissue with higher efficiency than the pure drug thus nanoparticulate system was efficient in mitigating the experimental colitis.
Keywords: Nanoparticles; Mesalamine; Inflammatory Bowel Disease; Eudragit RS100; PLGA; Eudragit RLPO